The Effectiveness of Public Demonstration Management in East Jakarta In Light of Law No. 9 Of 1998 - Muhammad Fauzi; Amsori Amsori (FOCUS, 2026)
This study aims to analyze the effectiveness of handling public demonstrations in East Jakarta in light of Law No. 9 of 1998 on Freedom of Expression in Public. Public demonstrations, as a manifestation of freedom of expression, constitute a constitutional right guaranteed by law; however, in practice, they often pose potential disruptions to public order and security stability.This research employs an empirical juridical method with a descriptive-analytical approach. It examines both the applicable legal provisions and their implementation in practice. Data were collected through literature review of laws and legal doctrines, as well as field research involving observations and interviews with law enforcement officials and relevant stakeholders. The data were analyzed qualitatively to assess the conformity between legal norms and their practical application in handling public demonstrations.The findings indicate that the handling of public demonstrations in East Jakarta has normatively referred to the provisions stipulated in Law No. 9 of 1998. Nevertheless, several challenges persist in its implementation, including limited inter-agency coordination, constraints in institutional resources, and low compliance among certain demonstrators with existing legal procedures. These issues contribute to the suboptimal effectiveness of demonstration management.